A Practical Approach to Make Computer Laboratory Courses more Effective and Interesting through Student Mentoring - Boregowda, Uma; Sunitha, P.; Geetha Kiran, A. (Journal of Engineering Education Transformations, 2017)
The prime job of an engineer is to manipulate energy,materials and information in order to create facilities and benefits for mankind. To perform this successfully, an engineer needs sound knowledge which is beyond mere theory and it also encompasses other life skills. The laboratory courses are an important part of professional and engineering undergraduate education; and they are the ideal place for active learning. Programming is an essential skill that must be mastered by anyone interested in studying computer science. Our experiences in teaching have proven that significant number of students find programming to be difficult and disheartening.This underlines the need for making the programming laboratory courses more effective, interesting and encouraging. In an attempt to achieve this, we have experimented students mentoring schemes during the laboratory classes. Student mentoring is just a form of support given to students, which has shown positive impact on their learning, thereby improving the quality of the engineering graduates. Few other methods are also proposed to make the laboratory course more professional and exciting.